2020
DOI: 10.5194/acp-2020-1040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling study of the impact of SO<sub>2</sub> volcanic passive emissions on the tropospheric sulfur budget

Abstract: Abstract. The contribution of volcanic emissions is argued as non-linear on the sulfur species burden. Thus, well constraining volcanic emissions inventories is necessary to better study the impacts induced by these pollution sources on the troposheric sulfur composition, as well as on sulfur species concentrations and depositions at the global surface. In this paper, the changes induced by the update of the volcanic sulfur emissions inventory on the global chemistry-transport model MOCAGE (MOdèle de Chimie At… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…They also suggested that marine biogenic sulfur was the dominant (approximately 84%) source of sulfate aerosols, but it is undeniable that other sources, such as volcanic sulfur from passive degassing presented by Lamotte et al. (2021), contribute to background sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…They also suggested that marine biogenic sulfur was the dominant (approximately 84%) source of sulfate aerosols, but it is undeniable that other sources, such as volcanic sulfur from passive degassing presented by Lamotte et al. (2021), contribute to background sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…The altitude of the mouth of the volcanoes is of course well known since a long time, and was taken into account already in the early global studies of the sulfur cycle, e.g. Spiro et al (1992), Pham et al (1995), Chin et al (2000). The crater lies generally much higher than the lowest level of the model.…”
Section: Some Additional Important Commentsmentioning
confidence: 99%